A non-covalent “click chemistry” strategy to efficiently coat highly porous MOF nanoparticles with a stable polymeric shell - Aykaç, Ahmet; Noiray, Magali; Malanga, Milo; Agostoni, Valentina; Casas-Solvas, Juan Manuel; Fenyvesi, Éva; Gref, Ruxandra; Vargas-Berenguel, Antonio (Biochimica et biophysica acta. General subjects, 2017)
Metal-organic framework nanoparticles (nanoMOFs) are biodegradable highly porous materials with a remarkable ability to load therapeutic agents with a wide range of physico-chemical properties. Engineering the nanoMOFs surface may provide nanoparticles with higher stability, controlled release, and targeting abilities. Designing postsynthetic, non-covalent self-assembling shells for nanoMOFs is especially appealing due to their simplicity, versatility, absence of toxic byproducts and minimum impact on the original host-guest ability. In this study, several β-cyclodextrin-based monomers and polymers appended with mannose or rhodamine were randomly phosphorylated, and tested as self-assembling coating building blocks for iron trimesate MIL-100(Fe) nanoMOFs. The shell formation and stability were studied by isothermal titration calorimetry (ITC), spectrofluorometry and confocal imaging. The effect of the coating on tritium-labeled AZT-PT drug release was estimated by scintillation counting. Shell formation was conveniently achieved by soaking the nanoparticles in self-assembling agent aqueous solutions. The grafted phosphate moieties enabled a firm anchorage of the coating to the nanoMOFs. Coating stability was directly related to the density of grafted phosphate groups, and did not alter nanoMOFs morphology or drug release kinetics. An easy, fast and reproducible non-covalent functionalization of MIL-100(Fe) nanoMOFs surface based on the interaction between phosphate groups appended to β-cyclodextrin derivatives and iron(III) atoms is presented. This study proved that discrete and polymeric phosphate β-cyclodextrin derivatives can conform non-covalent shells on iron(III)-based nanoMOFs. The flexibility of the β-cyclodextrin to be decorated with different motifs open the way towards nanoMOFs modifications for drug delivery, catalysis, separation, imaging and sensing. This article is part of a Special Issue entitled “Recent Advances in Bionanomaterials” Guest Editors: Dr. Marie-Louise Saboungi and Dr. Samuel D. Bader. •A non-covalent “click chemistry” strategy was developed to coat nanoMOFs.•Phosphorylated β-cyclodextrin derivatives efficiently coat nanoMOFs postsynthetically.•The higher the phosphate grafting density, the higher the coating stability.•The versatile coating does not affect the nanoMOF porosity, adsorption and release abilities.